Enhancing young graduates ‘intention towards halal entrepreneurship development in Brunei Darussalam: a case of Universiti Islam Sultan Sharif Ali - Khairul Hidayatullah Basir; Raihana Mohd Raff; Hafini Mahmud; Najihah Hanisah Marmaya (Academy of Contemporary Islamic Studies (ACIS) Universiti Teknologi MARA (UiTM), 2022)
Entrepreneurship involves creating ideas, generating innovative products or services, and problem-solving skills. However, entrepreneurial intention among the younger generation varies based on their behaviour from the aspect of psychological, environmental, cognitive, and demographic ones. Ultimately, understanding intention helps to grasp positive and encouraging factors towards starting a business. The purpose of this paper is to study the hala l preneur intention among UNISSA undergraduates who had undergone entrepreneurship courses in the university. In total, 85 respondents participated in a structural questionnaire to collect data and gather information on their social attitude towards the effectiveness of entrepreneurship education on their intention to start a business and become a halal preneur. The questionnaire results are analysed quantitatively to find out factors that motivate to become halal preneurs. On the implication aspect, it is hoped this research able to enhance and suggest foregrounding strategies to develop graduates’ intention towards becoming halal preneurs.